Sex-Specific Movement Responses of Reeves’s Pheasant to Human Disturbance: Importance of Body Characteristics and Reproductive Behavior - Shuai Lu; Zhengxiao Liu; Shan Tian; Kai Song; Qian Hu; Jianqiang Li; Jiliang Xu (Animals, 2022)
Human disturbance has a strong impact on the movement of wild animals. However, it remains unclear how the movement patterns of the Reeves’s Pheasant (Syrmaticus reevesii) respond to human disturbance in human-dominated landscapes. We tracked the movement of 40 adult individual Reeves’s Pheasants during the breeding season, and used the dynamic Brownian bridge motion model and kernel density estimation to analyze the diurnal movement patterns of Reeves’s Pheasants and their response to human presence. We analyzed the paths of Reeves’s Pheasants based on a partial least squares path model, considering habitat conditions, body characteristics, and reproductive behaviors. We found that males had two clear diurnal movement peaks, whereas reproductive and non-reproductive females did not show such movement peaks. Males shifted their movement peaks to earlier times in the day to avoid the presence peaks of humans. The correlation between human-modified habitat and the movement intensity of Reeves’s Pheasant differed between sexes. For males, the distance to forest paths had a positive correlation with their movement intensity through affecting body conditions. For females, the distance to forest paths and farmland had a negative correlation with their movement intensity through affecting habitat conditions and reproductive behaviors. Our study provides a scientific basis for the protection of the Reeves’s Pheasant and other related terrestrial forest-dwelling birds.